2014
DOI: 10.1371/journal.pone.0086337
|View full text |Cite
|
Sign up to set email alerts
|

Human and Mouse CD137 Have Predominantly Different Binding CRDs to Their Respective Ligands

Abstract: Monoclonal antibodies (mAbs) to CD137 (a.k.a. 4-1BB) have anti-tumor efficacy in several animal models and have entered clinical trials in patients with advanced cancer. Importantly, anti-CD137 mAbs can also ameliorate autoimmunity in preclinical models. As an approach to better understand the action of agonistic and antagonistic anti-CD137 mAbs we have mapped the binding region of the CD137 ligand (CD137L) to human and mouse CD137. By investigating the binding of CD137L to cysteine rich domain II (CRDII )and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…However, deletion of the first or second CRD diminished binding of 4-1BB-Fc to 4-1BBL (Supporting Information Fig. 1B), corresponding to a previous study also showed that both the first and second CRD are essential for the binding of 4-1BB-Fc to 4-1BBL [19]. We further evaluated the inhibitory activities of 4-1BB-Fc mutant molecules on sustained TNF production in vitro.…”
Section: Analysis Of Binding Activity Of 4-1bb-fc To 4-1bblsupporting
confidence: 71%
“…However, deletion of the first or second CRD diminished binding of 4-1BB-Fc to 4-1BBL (Supporting Information Fig. 1B), corresponding to a previous study also showed that both the first and second CRD are essential for the binding of 4-1BB-Fc to 4-1BBL [19]. We further evaluated the inhibitory activities of 4-1BB-Fc mutant molecules on sustained TNF production in vitro.…”
Section: Analysis Of Binding Activity Of 4-1bb-fc To 4-1bblsupporting
confidence: 71%
“…In contrast, 4-1BB/4-1BBL interactions are largely species-specific. Although h4-1BB does not bind to m4-1BBL, m4-1BB binds to h4-1BBL with greatly reduced affinity compared with that of h4-1BB (22). To understand the greatly restricted cross-species interactions, we compared the overall architecture of the respective 4-1BB/4-1BBL complexes (Fig.…”
Section: Comparison With the H4-1bb/4-1bbl Complexmentioning
confidence: 99%
“…Full-length SPLUNC1 cDNA was amplified by PCR and cloned into PCDM-L and PCDH-L, (13) which included the fragment of mouse IgG-Fc (mFc) and human IgG-Fc (hFc), respectively. The primers for the construction of PCDH-L-SPLUNC1 were: 5¢-CGCAAGCTTCAGATACTAAGAGC AAAGATG-3¢ and 5¢-CGCAGATCTGACCTTGATGACA AACTGTAG-3¢.…”
Section: Production Of Fusion Proteinmentioning
confidence: 99%
“…The purity of the fusion protein was confirmed by spectrophotometer (UV-2550, Shimadzu, Kyoto, Japan) and SDS-PAGE gel electrophoresis. A control fusion protein mE3-hFc, which was mouse CD137 cysteine-rich domains with human IgG-Fc, was produced by our laboratory, (13) and another control of human IgG1-Fc protein was purchased from Sino Biological (Beijing, China).…”
Section: Production Of Fusion Proteinmentioning
confidence: 99%
See 1 more Smart Citation